“Artful Sustainability” Inquiry into Urban Waste and Public Space Practices: a Case Study of Riverside View Mega City, Johannesburg - Mantshoane, Trevor (University of the Witwatersrand, Johannesburg, 2024)
The UN-Habitat (2021a, p. 29) has been spearheading efforts at ensuring that “placemaking institutionalizes the role of art and culture to achieve a lasting sense of place for [communities]” as per the SDG 11 agenda. Place-making foregrounds the central role of communities in ensuring quality and liveable public spaces often through arts-led interventions. To date, little research exists on how this global place-making agenda is faring at the neighbourhood level. Even less studied are the arts and cultural (ecosystem) services of public space and the impact of waste on people’s ability to benefit from these services. Against the global place-making agenda, this research artistically interrogates the eco-cultural dimensions of sustainability issues of waste and public spaces. It does this through a case study of Riverside View Mega City, Johannesburg (South Africa) This qualitative research study uses a case study strategy and draws on a range of practices broadly associated with the arts-based and practice- based methods. The study utilises a set of methodological tools like drawings, written and photo diaries to gain a window into the resident participants’ embodied experiences of waste and public space. In all, the research finds that waste malpractices have a disruptive impact on the residents’ ability to benefit from the eco-cultural services of public spaces in Riverside View Mega City. Consequently, public spaces are generally perceived and experienced negatively, although this is not uniform across all sections of the settlement. Moreover, efforts at institutionalising the arts and culture through place-making interventions remain ambiguous with little apparent relevance to the everyday sustainability issue of waste and public spaces.
A research report submitted in fulfillment of the requirements for the Master of Urban Studies, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Public space; Art; Artful Sustainability; SDG-15: Life on land